Present and future resilience research driven by science and technology. (14th June 2021) - Domaneschi, Marco; Cimellaro, Gian Paolo; Xie, Lili; Bruneau, Michel; Wu, Zhishen; Didier, Max; Noori, Mohammad; Mufti, Aftab A.; Lu, Xilin; Lu, Xinzheng; Ou, Jinpin; Sheikh, Shamim; et al.
Community resilience against major disasters is a multidisciplinary research field that garners an ever-increasing interest worldwide. This paper provides summaries of the discussions held on the subject matter and the research outcomes presented during the Second Resilience Workshop in Nanjing and Shanghai. It, thus, offers a community view of present work and future research directions identified by the workshop participants who hail from Asia - including China, Japan and Korea; Europe and the Americas.